Eksistensi Taman Nasional Bukit Dua Belas dalam Pelestarian dan Pemberdayaan Lingkungan Hidup Suku Anak Dalam - Doni Nofra; Fikri Surya Pratama; Attohiroh (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
The presence of Suku Anak Dalam (SAD) community within the Bukit Duabelas National Park (TNBD) area is inextricably linked to the park's management and existence. The SAD people live a nomadic lifestyle and rely on the natural resources within the park for their survival. This research will explain the TNBD management as an environmental protection, encompassing flora, fauna, and the habitat of SAD. This research is qualitative research and conducted at the Resort 2E TNBD area and the TNBD central office in Sarolangun City. The data collection techniques employed were field observation, interviews, documentation and a literature review. The data analysis employed triangulation techniques. The findings of this research demonstrate that effective management of the TNBD area necessitates a focus on maintaining the equilibrium of the ecosystem and the aspects of the lives of the Anak Dalam Tribe. As a biosphere reserve area with SAD in its vicinity, the Jambi regional government has been assisted by relevant partners and has actively involved SAD personnel and cultural aspects. The process commenced with the designation of national park zoning, proceeded with the protection of forest areas, and culminated in the empowerment of communities situated in the vicinity of Bukit Duabelas National Park.